The significance of interconnector counter-trading in a security constrained electricity market. (December 2015) - Higgins, P.; Li, K.; Devlin, J.; Foley, A.M.
Abstract: Throughout the European Union there is an increasing amount of wind generation being dispatched-down due to the binding of power system operating constraints from high levels of wind generation. This paper examines the impact a system non-synchronous penetration limit has on the dispatch-down of wind and quantifies the significance of interconnector counter-trading to the priority dispatching of wind power. A fully coupled economic dispatch and security constrained unit commitment model of the Single Electricity Market of the Republic of Ireland and Northern Ireland and the British Electricity Trading and Transmission Arrangement was used in this study. The key finding was interconnector counter-trading reduces the impact the system non-synchronous penetration limit has on the dispatch-down of wind. The capability to counter-trade on the interconnectors and an increase in system non-synchronous penetration limit from 50% to 55% reduces the dispatch-down of wind by 311 GW h and decreases total electricity payments to the consumer by €1.72/MW h. In terms of the European Union electricity market integration, the results show the importance of developing individual electricity markets that allow system operators to counter-trade on interconnectors to ensure the priority dispatch of the increasing levels of wind generation. Highlights: Interconnector counter-trading reduces the system marginal price in the SEM. Dispatch-down of wind power is reduced due to interconnector counter-trading. A 5% increase in the SNSP limit can reduce wind power dispatched-down by 50%. An increase in the SNSP limit and installed wind capacity reduces the SMP.